Beyond safety - Aase, Emily Johansen (Bloomsbury Publishing, 2021)
Introduction – 1. Risk and Proximity – 2. Risk and Embodiment – 3. Risk and Scale – 4. Risk, Action, and Sympathy – Bibliography – Index.
10.5040/9781501377044
Keywords: Electronic books; Fiction; Risk; Cosmopolitanism in literature; Globalism in literature; Neoliberalism in literature; Comparative Literature (Lit Studies); Contemporary Literature (Lit Studies); Literary Studies; Modern & contemporary fiction (post c 1945); Literary criticism